LESYA UKRAINKA AND VASYL STEPHANYK: TO THE HISTORY OF RELATIONSHIPS - Романов , С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article deals with the historical and literary plot of Lesya Ukrainka’s and Vasyl Stephanyk’s relationship, foundation due to their relations biography and (partly) creativity. The perception of reality, first for the master’s dark fields peculiarities of to the reactions world, particularly in contacts with people. Most substantially it influenced the perception of psychologicallynear persons where mutual understanding, not speaking about fellowship or friendship was complicated by the nery that that under different conditions. Had to facilitate rapprochement. It is about strikingly consonant spiritually and. To a certain extent, even eventful life circumstances and their retranslation / sublimation in creative work. Obviously, closer relations would give much each of the writers, but the power of repulsion of both identically charged worlds appeared more powerful than force of attraction.